Odpowiedzi

Najlepsza Odpowiedź!
2010-04-05T21:57:05+02:00
W(-2)=0
W(3)=0

0=(-2)³+a(-2)²+b
0=3³+a3²+b

0=-8+4a+b
0=27+9a+b

0=8-4a-b
0=27+9a+b

0=35+5a
-35=5a
a=-7

0=8+28-b
b=36

W(x)=x³-7x²+36
W(x)=(x+2)(x-3)(x-z)
(x+2)(x-3)(x-z)=x³-7x²+36
(x-z)(x²-3x+2x-6)=x³-7x²+36
(x-z)(x²-x-6)=x³-7x²+36
x³-x²-6x-zx²+zx+6z=x³-7x²+36
x³-x²(1+z)-x(6-z)+6z=x³-7x²+36
6z=36
z=6

Odp. a=-7, b=36, trzeci pierwiastek wynosi 6.
5 2 5
  • el21
  • Początkujący
2010-04-05T22:00:46+02:00
0=-8+4a+b ∧ 0=27+9a+b
b=8-4a ∧ 0=27+9a+8-4a
--||--- ∧ -35=5a
---||--- ∧ a=-7
b=8+28 ---> b=36

W(x)=x³-7x²+36
trzeci pierwiastek : 3
27-62+36=0
3 1 3